Urban land restitution in Cape Town: demanding the return of land rights in Constantia and Kensington/Ndabeni - Donaldson Ronnie; Hyman Glen; Chang David; Confiado André; Ruiz Ana María; Salud Ssicarú; Yildiz Sanem (Bulletin of Geography. Socio-Economic Series, 2014)
One of the hallmark policies implemented post-apartheid, the Restitution of Land Rights Act 22 of 1994, is a rights-based program aimed at addressing the loss of land resulting from past racially discriminatory laws or practices. The aim of this research was to identify what are the factors that determine the different outcomes of the restitution process when claimants are demanding the return of land rights and to highlight the challenges regarding the implementation of this land restitution policy. Focusing on two specific yet contrasting areas in Cape Town, Constantia and Kensington, it was determined that due to factors pertaining to the lands in question, the neighborhood surrounding the lands, the claimants, as well as the organization, function, and performance of different public entities, the policy has managed to fulfill restorative justice, but has yet to fulfill its ultimate goal of returning land rights to the claimants and undoing the injustices of the apartheid regime.